PENGEMBANGAN BAHAN AJAR SPLDV (MASTERING MATH) BERBASIS MOBILE LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA SISWA - sri susantini; lilis chotimah; ani nuraini; poppy yaniawati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Mathematics is the lesson that not to interest of student. It is also a reflection for teachers to make the learning process more interesting and meaningful, so that students can develop mathematical literacy skills. The learning process can be carried out using a context that is designed on a mobile learning-based teaching material by utilizing technological devices such as smartphones that are already used by students, but the benefits are not maximized. This development research aims to produce mobile learning based teaching materials on SPLDV material to see the increase in students' mathematical literacy skills. Guided by the steps of the Rowntree development model. This development model is grouped into three stages of development, the stage stage, stage stage, stage stage, and evaluation stage. At the evaluation stage, the researcher used Tessmer's formative evaluation model, namely: (1) self evaluation; (2) expert review; (3) one-to-one evaluation; (4) small group evaluation; and (5) field testing. With data collection techniques in the form of: new interviews, questionnaires for material experts, questionnaires for media experts, questionnaires for student responses, and test instruments. The subjects of this study were students of class VIII at SMPN 23 Bandung. The results showed that the mobile learning-based SPLDV teaching materials developed were valid and feasible as a source of mathematics learning and were effective in improving students' mathematical literacy skills.